2020
DOI: 10.3390/polym12122765
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication and Characterization of PEEK/PEI Multilayer Composites

Abstract: Polyetheretherketone (PEEK)/polyetherimide (PEI) blends (50/50, v/v) keeping the crystal phase of PEEK have been manufactured by alternate PEEK/PEI layer stacking. This strategy avoided the complete miscibility of both polymers, keeping layers of PEEK and PEI unmixed along the sample thickness, as well as promoting the formation of a smooth interfacial layer where PEEK and PEI were mixed. The properties of this interface after processing at molten state and different times was studied by DSC, DMA, and X-Ray sy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
11
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 33 publications
1
11
1
Order By: Relevance
“…This reduction is due to the mixture of polymer chains that occurs at the interface, where PEI chains hinder the crystallization of PEEK. However, this effect is less pronounced at 350 C in comparison to that observed at 380 C in our previous research [ 33 ]. The part of the curve corresponding to the cooling ramp confirmed these observations, such as in the lower crystallization enthalpy (28.7 J/g for 120 min vs. 29.9 J/g s for 10 min) or in the small shifts observed in the glass transition.…”
Section: Results and Discussioncontrasting
confidence: 87%
See 2 more Smart Citations
“…This reduction is due to the mixture of polymer chains that occurs at the interface, where PEI chains hinder the crystallization of PEEK. However, this effect is less pronounced at 350 C in comparison to that observed at 380 C in our previous research [ 33 ]. The part of the curve corresponding to the cooling ramp confirmed these observations, such as in the lower crystallization enthalpy (28.7 J/g for 120 min vs. 29.9 J/g s for 10 min) or in the small shifts observed in the glass transition.…”
Section: Results and Discussioncontrasting
confidence: 87%
“…Then, the limited interdiffusion of the PEEK/PEI layers was confirmed even after a long processing time. As this is a temperature-driven process, the interpenetration of polymer chains between these layers was much slower than that in our previous work at higher processing temperatures [ 33 ]. These results are in contrast to those obtained at around 400 C by other authors, where only one glass transition was observed in DMA tests due to the high degree of mixture induced on the PEEK/PEI blends at this processing temperature [ 12 , 40 ].…”
Section: Results and Discussionmentioning
confidence: 80%
See 1 more Smart Citation
“…The experiments indicated that as the time duration of hot-pressing increased, the bending displacement of the Al/Ni multilayered composite improved first and then declined sharply. Alvaredo-Atienza, et al [ 23 ] fabricated polyetheretherketone (PEEK)/polyetherimide (PEI) multilayered composites by alternating PEEK/PEI layer stacking to avoid the complete miscibility of both polymers, keeping PEEK layers and PEI layers un-mixed along the thickness direction, as well as accelerating the formation of a smooth interfacial layer between PEEK and PEI layers. The results revealed that although the interface between the two pristine polymers remained unchanged after the long processing time, the mechanical properties including the Young modulus, tensile strength, and strain at break of the PEEK/PEI multilayered films were improved compared to the original PEEK and PEI films.…”
Section: Introductionmentioning
confidence: 99%
“…[35] Polyetheretherketone (PEEK) is the most successful polyaryl ether ketone resin developed so far, thanks to the combined advantages of ether bonds, ketone groups and aromatic groups along the macromolecular backbone, PEEK exhibits superior mechanical capabilities of especially impact toughness, high radiation resistance, and temperature resistance. [36,37] Therefore, PEEK possesses enough excellent properties to be the matrix of EMW absorbing materials. For the composition of the absorbent, the magnetic FeCo alloys are not only soft-magnetic materials with large saturation magnetization, obvious Snoek's limit, high magnetic anisotropy energies, and great coercivity, but also have a size of approximate 1 μm, which are similar to the pores of the PEEK foam, so that the FeCo alloys can completely occupy the pores of the PEEK foam to achieve relatively strong absorption capacity.…”
Section: Introductionmentioning
confidence: 99%